127k views
4 votes
What is the value of x in the proportion StartFraction 6 x plus 1 over 7 EndFraction equals StartFraction 18 x minus 2 over 14 EndFraction?

A. 0
B. 3
C. two-thirds
D. one-fourteenth

User Malx
by
7.0k points

2 Answers

3 votes

Answer:

C

Step-by-step explanation:

.....................................................................

User Dhanunjay Mamidi
by
7.3k points
4 votes
The correct answer is: [C]: " two-thirds " .
____________________________________________________
" x = "
(2)/(3)
" ; which is: " two-thirds " .
____________________________________________________
Step-by-step explanation:
____________________________________________________

Given: "
(6x + 1)/(7) = (18x-2)/(14) " ; Solve for "x" ;
____________________________________________________
First, multiply the first fraction by "
(2)/(2)" ;
{ since: "
(2)/(2) = 1" ; and since any value, multiplied by "1" results in that exact same value. By multiplying the first fraction by: "
(2)/(2)" , we can get the "denominator" in the first fraction equal to the "denominator" of the second fraction.


image" .
___________________________________________________________
Note the "distributive property of multiplication" :
_______________________________________________________
a(b + c) = ab + ac ;

a(b – c) = ab – ac .
_______________________________________________________
As such, take the "numerator" ; which is:

" 2(6x + 1) " ; and expand:

→ = (2*6x) + (2*1) = " 12x + 2 " ;

Now, we can rewrite the entire expression:
________________________________________
"
(12x+2)/(14)" ; and we can rewrite the entire equation:
________________________________________

→ "
(12x+2)/(14) = \frac{18x-2}{14} [/tex] " ;

Let us simplify this: " 12x + 2 = 18x – 2 " ; Solve for "x" ;
_____________________________________________________

→ 18x – 2 = 12x + 2 ;

→ Subtract "12x" from each side of the equation; and subtract "2" from each side of the equation:


→ 18x – 2 – 12x – 2 = 12x + 2 – 12x – 2 ;

to get:

→ 6x – 4 = 0 ;

Add "4" to each side of the equation:

→ 6x – 4 + 4 = 0 + 4 ;

to get:

→ 6x = 4 ;

Divide each side of the equation by "6" ;
to isolate "x" on one side of the equation; & to solve for "x" ;

→ 6x / 6 = 4 / 6 ;

→ x = 4/6 ; "4/6" = "(4÷2)/(6÷2)" = "2/3" .

x = 2/3 ; x = "
(2)/(3)
" ; which is "two-thirds" ;

which is: Answer choice: [C]: " two-thirds" .
__________________________________________________________
User Nordin
by
7.6k points